Is Circular Fibrin Sealing of Low Rectal Anastomosis Able to Prevent Leakage in 21-Day Follow-up? Randomized Experimental Trial in Pigs. (August 2019) - Wenger, Frank Axel; Szucsik, Eduard; Hoinoiu, Bogdan Florin; Cimpean, Anca M.; Matonick, John P.; Ionac, Mihai; Raica, Marius
Purpose . Clinically apparent anastomotic leakage (AL) after low anterior rectal resection (LAR; <7 cm from anal verge) using circular double-stapled anastomosis without defunctioning stoma is up to 37.5%. However, it is unclear whether there is reduction of LAR after 21 postoperative days without defunctioning stoma but with extraluminal anastomotic application of fibrin sealant. Methods . Forty-eight-week-old pigs underwent LAR and circular double-stapled anastomosis in end-to-end technique (descendo-rectostomy). Animals were randomized into therapy and control group (cg). Therapy group (n = 20) received additional extraluminal circular anastomotic application of fibrin sealant. Objective was to assess incidence of clinically apparent and nonclinically apparent leakage through the 21st postoperative day. Remaining animals were sacrificed on the 21st day, and anastomotic region was analyzed. In case of earlier diagnosed AL, animals were sacrificed. Results . In cg, we observed clinically and nonclinically AL in 20% (n = 4). No animal was identified with a nonclinical-apparent leakage in this group, and all 4 animals with leakages presented clinical signs. In the therapy group, no animal (0/20) developed clinically apparent leakage signs. There were no leakages in this group, but 3 animals had ulcerative lesions without leak and without clinical signs. These lesions were observed intraluminally at crossing of staple lines after 21 days. In one of these animals, incomplete leakage was observed, blocked by fibrin sealant. Conclusion . In circular stapled colorectal anastomosis, circular fibrin glue sealant successfully protected anastomotic intraluminal wall defects at crossing of staple lines, reducing leakage rate from 20% to 0% (cg vs therapy group) after 21 postoperative days.